Independence and strong willed traits on Quinn as main character in Wolfsbane webtoon - Affan Jauza; Nurbaity (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
This study examines how a female protagonist, Quinn, is constructed through “masculinity” in the webtoon Wolfsbane. Using a qualitative, descriptive-analytic approach, it analyzes 11 panels from the prologue through episode six, combining textual dialogue and visual design. Drawing on Kress and van Leeuwen’s social semiotics, the study interprets representational, interpersonal, and compositional meanings (e.g., angle, salience, framing, color, and symbolic attributes) to trace how the narrative positions Quinn as an experienced werewolf hunter. The findings indicate that Quinn consistently displays independence and strong-willed determination—traits conventionally coded as masculine—through her attire, weapons, gaze, and forceful language. While traces of femininity remain, they are marginal compared with the dominant portrayal shaped by harsh training and her inherited mission.